RANCANG BANGUN SISTEM PERPIPAAN "RAKE" PADA ALAT VISUALISASI ALIRAN DI LABORATORIUM AERODINAMIKA - Zuhri, Mochamad Saifudin; Wailanduw, A. Grummy (Jurnal Rekayasa Mesin, 2021)
Fluid mechanics is a scientific discipline, which is part of the field of applied mechanics which studies the behavior of liquids and gases in a state of rest or motion. Fluid mechanics can be divided into fluid statics, fluid kinematics, and fluid dynamics. Fluid dynamics are fluid mechanics which study fluids in motion, especially liquids and gases. Fluid dynamics has a wide range of applications. Examples are used in calculating forces and moments on aircraft, mass flow rates of petroleum in pipelines, and forecasting weather patterns. Fluids are substances that can flow which have small to invisible particles and they can easily move and change shape without mass separation. Flow visualization is used to make the flow pattern of fluid (one of which is air) visible in order to obtain accurate data. The purpose of this research is to create a smoke generator that can spray smoke continuously. The method used in engineering is to vary the distance between the output pipes (tubes). There are three variations of rake used with each distance between the output pipes (tubes) of 60 mm (5 pieces), 42 mm (7 pieces), and 30 mm (9 pieces). The diameter of the outlet pipe (tube) and the main pipe (manifold) are made the same. The results of this engineering show that with variations in the distance between the output pipes (tubes) on the rake, different visualization results are obtained. In the 9 output pipe variations, the smoke output (streamline) is better than the other two versions, it can be seen from the visualization of the flow at the stagnation point and the flow is deflected to the upper and lower surfaces. While the visualization of the flow behind the vehicle there is not too much change because it does not vary the angle of the diffuser.